2018
DOI: 10.1111/jai.13845
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of star and cyp19 and plasma sex steroid during gonad development from previtellogenesis to early atresia in captive Sterlet sturgeon,Acipenser ruthenus

Abstract: Summary The aromatase cytochrome P450 family 19 (cyp19a) and Steroidogenic acute regulatory protein (star) mRNA levels were investigated in the ovarian follicles of captive Sterlet sturgeon, Acipenser ruthenus by real‐time PCR, and also plasma sex steroid levels and cortisol were measured throughout oogenesis from previtellogenic (PV) to early atresia. Thirty two females divided into four groups including PV, vitellogenic (VTG), post‐vitellogenic (POV) and atresia by histological studies. Blood samples were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The gender of fish exhibits significant plasticity, being influenced not only by genetic factors but also potentially by certain intrinsic or extrinsic factors, particularly sex steroids [22]. Hsd17b enzymes play a crucial role in the biosynthesis of sex steroids, acting downstream in the hormone synthesis pathway and involved in the interconversion of E1, E2, A, and T [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender of fish exhibits significant plasticity, being influenced not only by genetic factors but also potentially by certain intrinsic or extrinsic factors, particularly sex steroids [22]. Hsd17b enzymes play a crucial role in the biosynthesis of sex steroids, acting downstream in the hormone synthesis pathway and involved in the interconversion of E1, E2, A, and T [19].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the synthesis and metabolism pathway of sex steroid hormones in fish is a hot research topic. However, related research primarily focuses on the aromatase gene cyp19a [22] and some genes in the steroid hormone synthesis pathway, such as StAR2 [23] and cyp11a [24]. Research on the Hsd17b family genes has been mainly concentrated in mammals, where their expression levels and genotypes are closely associated with various diseases [25].…”
Section: Introductionmentioning
confidence: 99%
“…Sex steroid hormones, especially androgen and E 2 , play an important regulatory role in reproductive activities such as sex determination, gametogenesis, and storage in turtles and other vertebrates [ 45 , 46 , 47 ]. In the gonadal transcriptome of P. sinensis , cyp19a1 , cyp11a , hsd3b , hsd11b2 , and hsd17b7 were found to be significantly enriched in steroid hormone biosynthesis and ovarian steroid hormone genesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the gonadal transcriptome of P. sinensis , cyp19a1 , cyp11a , hsd3b , hsd11b2 , and hsd17b7 were found to be significantly enriched in steroid hormone biosynthesis and ovarian steroid hormone genesis pathways. Previous studies have shown that star , cyp11a1 , and hsd3b are closely related to gonadal development and gametogenesis in fish [ 45 , 48 , 49 ]. Hsd11b2 is involved in the synthesis of androgen 11-kT, and it plays an important role in the male sex differentiation of vertebrates such as Epinephelus coioides [ 50 ] and Cynoglossus semilaevis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%